Fatal human babesiosis caused by Babesia divergens in an asplenic host. (2018) - Kukina, Irina V.; Guzeeva, Tatiana M.; Zelya, Olga P.; Ganushkina, Ludmila A.
Highlights: The significance of human babesiosis, caused by the bovine pathogen Babesia divergens, a zoonotic, tickborne disease, can have a severe course with immunocompromised patients which usually ends up with death. Falciparum malaria was falsely diagnosed due to the fulminant course of a disease, clinical manifestation and to the presence of small ring forms of the parasites inside the erythrocytes. The differential diagnosis is important as the specific cure is different for these two diseases. The main morphological differences were pointed out between Babesia and Plasmodium using the original microphotograph. Abstract: We report a fatal case of human babesiosis caused by bovine pathogen Babesia divergens in Russia. Falciparum malaria was falsely diagnosed due to the presence of small ring forms in the blood smear. Laboratory diagnosis can distinguish between babesiosis and malaria according to the examination of stained blood smears.